MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Azmi, Ulil; Ridha DS, Muhammad (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2018)
Abstract: This study aims to explore and analyze the principal's management in improving the quality of education at MAS Thawalib Tanjung Limau. The approach used in this research is qualitative research approach by using field research type (field research). The subject of the study was the principal at MAS Thawalib Tanjung Limau. Data collection is done through observation, interview and documentation study. The analyst technique used is as follows: (1). Data reduction, (2). Presentation of data, (3). After the data is compiled and then drawn conclusions in the form of matrices and narratives. The results show that with good management, there is a quality improvement in MAS Thawalib Tanjung Limau, this is proven, with many events that have been successfully implemented in order to improve the quality, such as camps and provincial and provincial silat martial arts ever held at MAS Thawalib Tanjung Limau.